Association between metabolic syndrome and the risk of glaucoma: a meta-analysis of observational studies - Fei Li; Yanjun Luo; Xin Li; Yan Dai; Qingping Xiang (Diabetology & Metabolic Syndrome)
Abstract Background The potential link between metabolic syndrome (MetS) and the risk of glaucoma has been proposed but remains inconclusive. This meta-analysis aimed to systematically evaluate the association between MetS and the risk of glaucoma. Methods We conducted a comprehensive search of PubMed, Embase, and Web of Science from inception to August 12, 2024, for observational studies assessing the relationship between MetS and glaucoma risk. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to estimate the association. Heterogeneity was assessed using I² statistics, and a random-effects model was applied. Results Nine studies involving 2,258,797 participants were included. The pooled results showed that MetS was significantly associated with an increased risk of glaucoma (OR: 1.34, 95% CI 1.15–1.55, p < 0.001; I² = 75%). Subgroup analyses according to the individual component of MetS suggested that hypertension and hyperglycemia were significantly associated with glaucoma, but not for obesity or dyslipidemia, although the difference among subgroups was not significant (p = 0.05). Further subgroup and meta-regression analyses suggested that the results were not significantly affected by study design, average age, sex, method of glaucoma diagnosis, or glaucoma subtype (primary open-angle glaucoma or normal-tension glaucoma). Sensitivity analysis confirmed the robustness of the findings. Conclusions This meta-analysis suggests that MetS is significantly associated with an increased risk of glaucoma. These findings highlight the need for heightened awareness and potential screening strategies for glaucoma in individuals with MetS. Further studies are required to elucidate underlying mechanisms and causality.